Let's analyze the steps from Henry's solution to identify where he went wrong.
The original equation is: \[ 4 \left(-\frac{1}{2} x + 7\right) + 5x = 15 \]
Step 1:
Henry writes: \[ -2x + 28 + 5x = 15 \]
The left side should be calculated using the distributive property: \[ 4 \left(-\frac{1}{2} x + 7\right) = 4 \cdot -\frac{1}{2}x + 4 \cdot 7 = -2x + 28 \] So, this step is correct, as Henry applied the distributive property correctly.
Step 2:
Henry then writes: \[ 3x + 28 = 15 \]
He combines \(-2x\) and \(5x\) correctly: \[ -2x + 5x = 3x \]
This step is also correct.
Step 3:
Henry writes: \[ 3x = 15 - 28 \] From here, Henry simplifies incorrectly. The correct operation would be: \[ 3x + 28 = 15 \implies 3x = 15 - 28 \implies 3x = -13 \] So this step is incorrect as he did not subtract 28 correctly from 15.
Step 4:
Henry then writes: \[ x = 5 \]
Since he derived \(3x = 15\), he would get \(x = 5\) based on the incorrect earlier step.
In conclusion, the error arises in Step 3 where the subtraction from 15 was handled incorrectly, leading to Henry's incorrect solution.
The correct explanation for why Henry’s solution is incorrect is:
Step 3 is wrong because the subtraction property of equality was used incorrectly.